CoCo Bonds, Bank Stability, and Earnings Opacity - Melina Ludolph (Halle Institute for Economic Research (IWH), 2024)
This paper examines the effect of CoCo bonds that qualify as additional tier 1 capital on bank stability and reporting. The results reveal a significant reduction in the distance to insolvency following the hybrid bond issuance due to increased earnings volatility. Banks report less stable net income due to more volatile loss provisions, which increases earnings opacity rather than reflects changes in asset quality. The findings are consistent with the premise that persistent uncertainty and misconceptions among investors about bail-in likelihoods limit their monitoring engagement, which results in banks becoming less transparent.
Keywords: G21; G28; G32; M41; 330; AT1 capital; bank stability; Basel III; CoCo bonds; earnings opacity